Substantiation of the perspectivity of improving of the population informing about the criteria of the correct choice of modern multivitamin drugs - Kutsenko, Tetiana; Semeniv, Dmitro; Shchokina, Katherina; Belik, Galina; Stoletov, Yurii; Getalo, Olga (ScienceRise: Biological Science, 2021)
The aim. Determination of the need to raise awareness of the population about multivitamins and the criteria for their rational choice. Materials and research methods. To achieve the goal of the study, it was necessary to develop a questionnaire for visitors to pharmacies and carry out an anonymous survey of them. All adult visitors of the pharmacy were attracted to the survey. The developed questionnaire consisted of 3 parts and contained 32 questions processed in the course of our own research. Research results. Among the pharmacy visitors we surveyed, the majority were between the ages of 35–55, approximately equally divided were men and women who mainly lived in the Kiev region (87 %), were not students and did not have educational levels of bachelor or master, and had no relation in health care education. Summarizing the information obtained in the course of processing questionnaires with the answers of visitors to pharmacies, it can be noted that in the surveyed group of respondents there is a certain interest and indifference to the discussed aspects, but quite often there is a lack of knowledge in this regard. Conclusions. In the course of analyzing the results of the questionnaire survey, the level of awareness of the population regarding general information about the pharmacology of multivitamin drugs and the criteria for their correct choice was determined. From the data obtained, it can be concluded that on many issues the respondents showed an insufficient level of knowledge, which justifies the need for additional information about multivitamins, and indicates that better it should be done with participation of a specialist with a pharmaceutical education or physician. Mostly the population lacks knowledge on the issues listed in the second part of the questionnaire, namely, on general information about the biological and pharmacological properties of vitamins. It was found that the information obtained from the Internet or other media, including advertising, has a significant impact on the awareness and decision of the respondents